Four tier framework for online applications of 3D GIS visualization - Che Mat, Ruzinoor (2012)
The aim of this study is to discuss on the issues related to the use of a new proposed four-tier architecture for online applications of 3D GIS visualization. Conventional design of the system is generated from client/server based architecture. This architecture is the main platform for designing online system architecture, which works based on the distributing concept, which is a tier. The tier is normally set by the developers to separate the works/tasks between the system architecture. Currently, three tiers architecture is the most well-known architecture used in GIS applications and also other application. However, this architecture has some drawback on scalability, maintainability, and also its need more processing power in the middle tier to process the request from multiple of users. Based on the literature study, GIS applications, especially systems, which involve 3D visualization generate a massive amount of data. Due to this situation, the current three-tier architecture used for online application of 3D GIS visualization decrease the performance of the system in terms of time for processing the request from the users. This research explores the use of the four-tier framework to overcome current impediments in the use of the three-tier framework for online applications of 3D GIS visualization. The new framework is designed based on client/server architecture with the tasks distributed using the tier‟s concept. It is formalized into four tiers framework by advancing one more tier into the existing three tiers framework for handling the visualization process. The four tiers framework is divided into the client, logic, visualization process, and database tiers respectively. The unique part of this new architecture is the middle tier which is divided into two other tier‟s, which handle the visualization process and logical process separately and make the framework more flexible and increase its performance. The framework has been successfully implemented in oil palm plantations application using a prototype developed to prove that the framework functions well based on the requirements. Several experiment related to terrain visualization application conducted to give an operational guidelines for developer. The results of experiments helps developer on utilising the best data and technique for developing the required system. The prototype shows that it can aid the oil palm plantation management to visualize their plantation easily in 3D. The oil palm trees can be visualized with 3D terrain in an online environment with GIS capabilities. The characteristic of the oil palm tree data is stored in the database tier, and the data can be modified based on users need. The 3D terrain is generated from the topographic data (LiDAR Data) and overlaid with the high- resolution satellite image (QUICK BIRD). The validation of the framework was performed by comparing the results from the existing three-tier framework with the new four tier framework. The new framework shows superiority in its performance based on loading time, response time, frames per second, CPU usage and memory usage. These results show that the approach in this research helps solve the processing power problem. The framework can be applied by users to visualize a multitude of applications with GIS capabilities in an online 3D environment.